Improvement of BMD after Switching from Lopinavir/R Plus Two Nucleos(T)ide Reverse Transcriptase Inhibitors to Lopinavir/R Plus Lamivudine: OLE-LIP Substudy. Issue 3 (3rd May 2016) - Crespo, M.; Navarro, J.; Martinez-Rebollar, M.; Podzamczer, D.; Domingo, P.; Mallolas, J.; Saumoy, M.; Mateo, G. M.; Curran, A.; Gatell, J.; Ribera, E.
Abstract : Objective: To compare 48-week changes in bone mineral density (BMD) and body fat distribution between patients continuing lopinavir/ritonavir and two NRTIs and those switching to lopinavir/ritonavir and lamivudine. Methods: Substudy of a randomized, open-label, multicenter OLE study was carried out. Adult HIV-infected patients with <50 copies/mL for ≥6 months were randomized (1:1) to continue lopinavir/ritonavir and two NRTIs or switching to lopinavir/ritonavir and lamivudine. Dual-energy X-ray absorptiometry (DXA) was performed at baseline and after 48 weeks to measure bone composition and body fat distribution in both the groups. Results: Forty-one patients (dual-therapy, n  = 23; triple-therapy, n  = 18) of 239, who received at least one dose of study medication, completed the study: median age, 42 years, 71% male, 73% Caucasian. At week 48, total BMD increased by 1.04% (95% CI, 0.06 to 2.01%) among patients switching to dual-therapy, whereas no significant changes occurred in patients maintaining triple-therapy. Dual-therapy and older age were independently associated with total BMD increase. Among patients discontinuing tenofovir-DF, a significant increase was seen in total BMD (1.43; 95% CI, −0.04 to 2.91) and total hip (1.33%; 95% CI, 0.44 to 2.22%). A non-statistically significant decrease in femoral and spinal BMD was observed in patients who discontinued abacavir and in those continuing triple-therapy. Regarding fat distribution, no significant changes were seen in both the treatment groups. Discussion: BMD increased following switching to lopinavir/ritonavir plus lamivudine in HIV-infected patients on suppressive triple-therapy with lopinavir/ritonavir and two NRTIs including tenofovir-DF.